KINERJA KEUANGAN PERUSAHAAN TEKSTIL DAN GARMEN SEBELUM DAN SELAMA PANDEMI COVID-19 - Pattiruhu, Dionisius Christopher Septa Hernawan; Tanggulungan, Gustin (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya, 2024)
This study aims to obtain empirical evidence and compare the financial performance conditions of companies in the textile and garment industry before and during the COVID-19 pandemic. The textile and garment industry is in the third highest position of Indonesian industry. The research data is secondary data obtained from the Indonesia Stock Exchange. Using a purposive sampling technique, 10 textile and garment companies were selected in the 2018-2022 period. The data were analyzed using financial ratios including liquidity, solvency, profitability, and activity ratios. The Wilcoxon test was used to test the difference in the company's financial performance in the period before and during the Covid-19 pandemic with Microsoft Excel and SPSS 27. The results show that the financial performance of textile and garment companies in Indonesia during the observation period was quite diverse. The difference test informs of differences in DER and TATO. However, there was no difference in performance based on CR, QR, DAR, NPM, ROA, GPM, and ITO. Companies that made extensive asset investments before the pandemic showed worse DER and TATO during the pandemic. Companies that were innovative in producing PPE showed better performance.